The effect of maternal and fetal glucose homeostasis on birth weight. (16th November 2010) - Walsh, J; Mahony, R; Foley, M; Mc Auliffe, FM
Abstract : Aim: To examine the effect of glucose homeostasis on fetal growth. Methods: This is a prospective study of 340 healthy non-diabetic women. First trimester fasting glucose, 28-week fasting glucose, 34-week fetal growth and fetal anterior abdominal wall thickness (AAW) were recorded. At delivery cord glucose and birth weight was measured. Results: Maternal body mass index (BMI) correlated with maternal glucose, AAW and birth weight. Maternal weight gain in pregnancy was related to estimated fetal weight and birth weight. Maternal fasting glucose was positively correlated to cord glucose and birth weight. The incidence of macrosomia (>4.5 kg) was significantly greater for fasting glucose concentrations in the highest quartile compared to the lowest quartile. (20.1% vs 6.5%, p<0.05, first trimester; 23.3% vs 9.4%, p<0.05, at 28 weeks). Cord blood glucose was related to estimated fetal weight, AAW, birth weight, length and head circumference. Conclusion: Glucose homeostasis is an important determinant of both maternal and fetal size. Maternal glucose and BMI appear to be the factors driving fetal glucose and fetal size. Manipulation of maternal dietary carbohydrate may have a beneficial effect on fetal glucose homeostasis and fetal growth, and is worthy of further investigation.